Dissecting the relationship between heart failure and diabetic retinopathy severity in patients with diabetes and chronic kidney disease: an observational cohort study - Yi-Chen Huang; Feng-Ching Shen; Pei-Kang Liu; Wei-Chun Su; Teng-Hui Huang; Ming-Yen Lin; Mei-Chuan Kuo; Yi-Wen Chiu; Shang-Jyh Hwang; Yi-Ting Lin; Ping-Hsun Wu (Scientific Reports)
Abstract Diabetic retinopathy (DR) is associated with increased cardiovascular risk, but evidence of its relationship with heart failure (HF) in people with diabetes and chronic kidney disease (CKD) is limited. Therefore, we examined the association between DR severity and concurrent HF status, as well as the risk of subsequent HF hospitalization in this population. A total of 1,503 patients with both diabetes and CKD underwent fundus photography. DR severity was classified into three groups: Group 1 (no apparent DR, mild non-proliferative DR [NPDR], moderate NPDR), group 2 (severe NPDR, very severe NPDR), and group 3 (proliferative DR [PDR], and high-risk PDR). Associations between HF status and DR severity were analyzed using ordinal regression. Cox proportional hazard models examined the association between DR severity and subsequent HF hospitalization. HF was positively associated with worse DR grade (adjusted odds ratio 2.09, 95% confidence interval [CI] 1.37–3.18). In patients without HF at baseline, a higher incidence of acute HF hospitalization over 5 years was identified in group 2 (hazard ratio 1.37, 95% CI 0.83–2.26) and group 3 (hazard ratio 1.86, 95% CI 1.22–2.83) compared to patients with less severe DR. In summary, DR severity is independently associated with both concurrent HF and risks for HF hospitalization over 5 years among those with diabetes and CKD and could aid cardiovascular risk stratification.